2016
DOI: 10.2341/15-319-l
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties and Color Stability of Resin-Infiltrated Enamel Lesions

Abstract: Surface hardness of enamel lesions increased significantly after resin infiltration and remained stable following thermocycling. Surface roughness and color stability of resin-infiltrated enamel lesions were less than ideal and might further deteriorate after aging in the oral environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 46 publications
7
52
1
4
Order By: Relevance
“…Regarding surface roughness, our results agreed with previous studies which concluded that resin infiltration of enamel lesions can provide and maintain smoother surface. However, these results contrast those of other researches which reported that surface roughness and color stability of resin‐infiltrated enamel lesions were less than ideal and could further recede with aging in the oral environment. This disagreement may be a result of mismatching in the experimental conditions and evaluation methods.…”
Section: Discussioncontrasting
confidence: 94%
“…Regarding surface roughness, our results agreed with previous studies which concluded that resin infiltration of enamel lesions can provide and maintain smoother surface. However, these results contrast those of other researches which reported that surface roughness and color stability of resin‐infiltrated enamel lesions were less than ideal and could further recede with aging in the oral environment. This disagreement may be a result of mismatching in the experimental conditions and evaluation methods.…”
Section: Discussioncontrasting
confidence: 94%
“…The increased surface roughness observed on the resin-infiltrated lesions with aging in the present study, may be attributed to internal and thermal stresses generated by water sorption and thermal expansion and contraction. 19 The present results agreed with former studies [30][31][32] which reported the ability of resin infiltrants to provide and maintain smoother enamel surface. However, other studies 19,33,34 came in contrast, as they reported that surface roughness of resin-treated enamel lesions were not ideal and might further recede with aging.…”
Section: Discussionsupporting
confidence: 93%
“…The thermocycler was programmed to perform 5000 cycles (group 4) or 10,000 cycles (group 5) between two water baths at temperatures of 5ºC and 55ºC, respectively, with a dwell time of 30 seconds at each temperature. 19…”
Section: Thermocycling (Tc)mentioning
confidence: 99%
“…Moreover, infiltration of initial lesions will significantly strengthen the hardness of demineralised areas, 17, 18 thus providing a sound basis for any sealing restoration and potentially resulting in decreased failure rates. This feature is considered a further aspect of relevance.…”
Section: Discussionmentioning
confidence: 99%
“…A low-viscous resin infiltrant (RI) has been developed and penetrates and occludes the porous volume of subsurface lesions, 15, 16 thus significantly increasing the microhardness of demineralised enamel (and restoring hardness of sound enamel). 17, 18 Some preliminary investigations focussing on aspects of occlusal infiltration have presented promising outcomes both in vitro 19, 20 and clinically. 21 However, organic material (for example, proteins, 22, 23 lipids, 22, 24 and bacterial compounds 25 ) often block the pores of natural subsurface lesions.…”
Section: Introductionmentioning
confidence: 99%